2012
DOI: 10.1007/978-3-642-33709-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Quaternion-Based Spectral Saliency Detection for Eye Fixation Prediction

Abstract: In recent years, several authors have reported that spectral saliency detection methods provide state-of-the-art performance in predicting human gaze in images (see, e.g., [13]). We systematically integrate and evaluate quaternion DCT-and FFT-based spectral saliency detection [3,4], weighted quaternion color space components [5], and the use of multiple resolutions [1]. Furthermore, we propose the use of the eigenaxes and eigenangles for spectral saliency models that are based on the quaternion Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 39 publications
1
97
0
1
Order By: Relevance
“…Note that some recent high performing models (e.g., ∆QDCT [59], CovSal [60]) and benchmarking efforts were not considered here (e.g., [29,58]). Analysis of scores shows that CC and NSS suffer from center-bias and conclusions should not be based just on them.…”
Section: Discussionmentioning
confidence: 99%
“…Note that some recent high performing models (e.g., ∆QDCT [59], CovSal [60]) and benchmarking efforts were not considered here (e.g., [29,58]). Analysis of scores shows that CC and NSS suffer from center-bias and conclusions should not be based just on them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in [39], it has been shown that a static Gaussian blob has an average ROC score of 0.80 on the Toronto dataset, exceeding many state-of-the-art methods, without using any bottom-up features in the images. To control for these factors, we adopt the shuffled-AUC proposed by [34,39], which has become a standard evaluation method used in many recent works [33,14,3,10]. Under the shuffled-AUC metric, a perfect prediction will give an AUC of 1.0, while any static saliency map will give a score of approximately 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike models based on properties like contrast, rarity and symmetry, another family of saliency models are based on spectral domain analysis [15,14,33,27]. However, [27] shows that some previous spectral analysis based methods are in some sense equivalent to a local gradient operator plus Gaussian blurring on natural images, and thus cannot detect large salient regions very well.…”
Section: Related Workmentioning
confidence: 99%
“…by self-information [33], information maximization [5], or discriminant saliency that distinguishes target from null hypotheses [7]. Recently, spectrum-based methods demonstrated good performance despite low computational complexity [12,11,28].…”
Section: Imagementioning
confidence: 99%
“…As reference for comparisons, we consider 11 stateof-the-art saliency algorithms: GBVS [10], the multiscale quaternion DCT signature on YUV input (denoted ∆QDCT) [28], Judd [18], AWS [8], CovSal [6] (with covariances + means), Tavakoli [30], AIM [5], Goferman [9], ICL [13], Image Signature (with LAB color space) [11], and Boost [4], all with default parameters. This selection is based on the top-performing models from two recent and comprehensive reviews/taxonomies [4,16].…”
Section: Evaluation Protocolmentioning
confidence: 99%